Effects of Chronic Social Defeat Stress on Behavior and Dopamine Receptors in Adolescent Mice With 6-Hydroxydopamine Lesions of the Medial Prefrontal Cortex - Zhao, Tong; Gao, XiaoLei; Huang, Guang-Biao (Frontiers in Behavioral Neuroscience, 2021)
Background Social stress factors in schizophrenia have long-term effects, but will only induce symptoms in a portion of individuals, even if exposed to identical stress. Methods In the current experiment, we examined mice with 6-hydroxydopamine (6-OHDA)-induced medial prefrontal cortical (mPFC) injury to select for members of a “stress-susceptible group,” and observed changes in behavior and the expression of D1 and D2 dopamine receptors in amygdala and hippocampus. Results We observed that after chronic social defeat stress, 72.6% of 6-OHDA lesioned mice exhibited stress response to aggressors, compared to 52.3% of the blank control group. Both the 6-OHDA lesion+social defeat and social defeat groups exhibited anxiety and depression-like behavior. However, social cognitive impairment in mice from the 6-OHDA lesion+social defeat group was more significant and D1 expression levels in the amygdala were significantly decreased. Conclusions These results suggest that the reason that adolescent mice with cortical injury were highly sensitive to defeat stress and had more prominent social cognitive impairment may be decreased selectivity of D1 in the amygdala.